2015
DOI: 10.1097/gox.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

A Head-to-head Comparison between SurgiMend and Epiflex in 127 Breast Reconstructions

Abstract: Background:The use of acellular dermal matrices (ADM) has become a widely used option in breast reconstruction. A great deal of literature is available, totaling over 2400 ADM reconstructions. Nonetheless, head-to-head comparisons between SurgiMend and Epiflex are not yet reported. In fact, this is the first clinical data report on the use of Epiflex. This work will, therefore, compare postoperative complication rates and costs for these ADMs.Methods:This analysis is a retrospective review of a single surgeon’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
3
24
2
Order By: Relevance
“…Figure 3 shows a pooled analysis of complication rate data for SurgiMend ® , Epiflex ® and Tutomesh ® (10). We found complication rates to be low and comparable to literature in all cases.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Figure 3 shows a pooled analysis of complication rate data for SurgiMend ® , Epiflex ® and Tutomesh ® (10). We found complication rates to be low and comparable to literature in all cases.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the assumption that ADM type may not be an independent risk factor, it remains important to compare new products to existing data. Including this work there are only 5 available publications regarding the use of SurgiMend ® , and Tutomesh ® in breast reconstruction (Table II) (8,10,16,19). Within these studies, head to head comparisons were made to AlloDerm ® and Epiflex ® ; both products based on human tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported a significant difference in complication rate between the study group treated with SurgiMend and the control group. Eichler et al (2015) reported a significantly higher incidence of infection requiring intravascular antibiotics and overall complication rate in the group treated with Epiflex vs SurgiMend. In the study by Butterfield (2013) Review © 2020 MA Healthcare Ltd statistically significant higher number of subjects treated with AlloDerm suffered from seroma (P<0.05), while subjects treated with SurgiMend showed a higher rate of minor necrosis (P<0.05).…”
Section: Safety and Performance Outcomes Of Surgimendmentioning
confidence: 93%
“…In addition, nonbiological materials such as polyglactin meshes or titanized polypropylene meshes have been used. However, several clinical studies revealed no advantages of porcine ADM over human or bovine ADMs (Ball et al, ; Butterfield, ; Eichler et al, ; Glasberg & Light, ; Mazari et al, ; Ricci et al, ). With a wide variety of choice and no clinical evidence for superiority of porcine matrices over any other, the use of porcine acellular matrices is not required for Muslim patients.…”
Section: Plastic Surgerymentioning
confidence: 99%